2016
DOI: 10.1039/c6ra19618g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyaniline/graphene composites with excellent anti-corrosion properties and their application in waterborne polyurethane anticorrosive coatings

Abstract: Polyaniline, a novel conductive polymer, has been widely used as an anti-corrosive filler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 27 publications
1
63
0
Order By: Relevance
“…It was more environmentally friendly than traditional heavy metal and their oxide coatings. Recently, graphene has been reported to be an excellent anticorrosion material due to its unique characteristics of chemical inertness, excellent thermal and chemical stability, remarkable flexibility and impermeable to molecules [386][387][388]. Jafari et al [386] electrochemically synthesized adherent PANI/graphene nanocomposite coatings on Cu substrates.…”
Section: Corrosion Protectionmentioning
confidence: 99%
“…It was more environmentally friendly than traditional heavy metal and their oxide coatings. Recently, graphene has been reported to be an excellent anticorrosion material due to its unique characteristics of chemical inertness, excellent thermal and chemical stability, remarkable flexibility and impermeable to molecules [386][387][388]. Jafari et al [386] electrochemically synthesized adherent PANI/graphene nanocomposite coatings on Cu substrates.…”
Section: Corrosion Protectionmentioning
confidence: 99%
“…The corrosion rate (C.R.) can be obtained by substituting the corrosion current into the following equation [2]:…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The charge transfer resistance (R ct ) was obtained from the semicircular diameter in the real part of the Nyquist plot. The R ct value was substituted into the following equation to obtain the protection efficiency [2]:…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, chemical modification of the surface of graphene is necessary to satisfy the requirements for a particular application. A few studies have reported the application of functionalized graphene in anti-corrosion coatings [12][13][14].…”
Section: Introductionmentioning
confidence: 99%